ChemInform Abstract: Copper Catalyzed N‐Arylation of Amidines with Aryl Boronic Acids and One‐Pot Synthesis of Benzimidazoles by a Chan—Lam—Evans N‐Arylation and C—H Activation/C—N Bond Forming Process. Issue 19 (18th April 2013) - Li, Jihui; Benard, Sebastien; Neuville, Luc; Zhu, Jieping
Abstract Benzamidines are synthesized in two steps either via intermediate amidates or in a one‐pot procedure.